(untitled) (Research, Society and Development, 2022)
Neoplasms are among the major causes of human deaths from disease. And head and neck cancer is considered the main neoplasm that affects Brazil. During the oncological treatment of patients with head and neck involvement, several oral manifestations appear, and the intervention is up to the dentist. Therefore, it became the objective of this study to evaluate, through questions, the knowledge of dentists about the treatment of cancer patients, before during or after the chemo or radiotherapy intervention, in order to verify the level of knowledge of professionals for the care with cancer patients. The research was carried out with Dental Surgeons who work in their profession either in private or private clinics through an electronic form sent via specific groups through the WhatsApp application. 19 Dental Surgeons participated in the research, most of them specialists in Orthodontics, Dentistry for Patients with Special Needs and Public Health. The data obtained were computed and submitted to simple statistical analysis of quantification. As a result, the study identified a positive perception that professionals in the field of Dentistry do not feel prepared to care for cancer patients. It is concluded that Dental Surgeons are not prepared to assist patients undergoing cancer treatment, the research result confirmed a lack of knowledge among the interviewees.